E = MC2 + 1: A fully digital, collaborative, high-definition (HD) production from scene to screen - Lugmayr, Artur; Adrian, H.; Golebiowski, P.; Jumisko-Pyykko, S.; Ubis, F.; Reymann, S.; Bruns, V.; Kybartaite, A.; Kauranen, J.; Matthes, D. (2008)
This article presents a unique course for students, the course took place at the Tampere University of Technology (TUT) in the NAMU - - New AMbient MUltimedia research group. The basic idea was to create a five-minute production involving all the new technology available to the modern film-maker. We want to prove that even a non-experienced team of film-makers are capable of creating a short HD film with (almost) commonly available equipment. A full high-definition (HD) digital workflow was undertaken - - from scene to screen. In each production step, new technologies and approaches were tested to explore the world of digital film-making. In pre-production the movie-script was written collaboratively with Wiki tools. The participants' experience was evaluated, and the results are presented in this article. In production we focused on HD methods to create content and applied the Material eXchange Format (MXF) to handle metadata in production; the final movie was distributed via typical television channels, such as DVB-T, IP-TV, and DVB-H. The experimental results are presented in this article as well. In this article we present our experience in terms of technology, introduce a learning-by-doing concept during course development, and give a complete analysis of a full digital HD workflow. © 2008 ACM.